2021
DOI: 10.9734/jpri/2021/v33i58a34134
|View full text |Cite
|
Sign up to set email alerts
|

Ipsilateral Neck/Inter-Trochanteric and Mid-shaft Femoral Fractures Treated with Dual Construct Implants

Abstract: Background: Various management protocols for ipsilateral neck/intertrochanteric and shaft fracture femur have been formulated, there have been many disagreements related to their ideal fixation plan. The aim of this study was to discuss the various type of fixation system available for such kind of complex injuries and the advantages of using dual construct fixation system. Patient and Methods: In the present study we prospectively evaluated ipsilateral neck/intertrochanteric and shaft fracture femur in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“… D.I. Time to union PF (months) Time to union SF (months) Mean follow-up (range) Chaudhary et al (2021) [ 61 ] 2018–2020 7 (7) 5 (71%) 35 (27–45) 7 (100%) FN + TF N.A. 0 7 4.1 (3–6) 5.1 (3–11) 16.2 (10–22) Rana et al (2021) [ 62 ] 2018–2020 13 (13) 8 (62%) 38 (23–54) 13 (100%) FN N.A.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“… D.I. Time to union PF (months) Time to union SF (months) Mean follow-up (range) Chaudhary et al (2021) [ 61 ] 2018–2020 7 (7) 5 (71%) 35 (27–45) 7 (100%) FN + TF N.A. 0 7 4.1 (3–6) 5.1 (3–11) 16.2 (10–22) Rana et al (2021) [ 62 ] 2018–2020 13 (13) 8 (62%) 38 (23–54) 13 (100%) FN N.A.…”
Section: Resultsmentioning
confidence: 99%
“…Only seven studies reported sufficient data concerning operation time and perioperative blood loss [ 19 , 28 , 49 , 54 , 59 , 61 , 62 ]. Table 2 shows the pooled analysis for operation time and perioperative blood loss for both treatment groups.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The embryo goes through perforation at this time, the blastocoel is large enough to push the trophectoderm up against the zona pellucida, and the latter begins to thin. This is when the to cleavage is defined as the first observed frame in which the newly formed blastomeres are completely separated by epithelial cell membranes (11)(12)(13)(14)(15)(16)(17)(18)(19)(20).…”
Section: Data Collection (Image Capturing Related Morphology)mentioning
confidence: 99%